Religiosity, Spirituality, and Happiness in Thailand from the Perspective of Buddhism - Winzer, Lylla; Samutachak, Bhubate; Gray, Rossarin Soottipong (Journal of Population and Social Studies [JPSS], 2018)
Studies on the association between religiosity, spirituality, and happiness in the Buddhist context remain scarce despite the great number of followers of this religion around the world. Theravada Buddhism, as the dominant Buddhist sect in Thailand, has a strong influence on Thai people’s attitudes, thoughts, and way of life. The purpose of this study was to explore the link between religiosity and spirituality and level of happiness among the Thais. Data were pooled from national surveys on social and cultural issues in 2008 and 2011. The samples were 25,950 and 23,671 Thai people aged 15 years or older. The results revealed frequency of religious and spiritual practices was significantly associated with greater level of happiness, even after controlling for study year, demographic factors (age, sex, and marital status), and socioeconomic factors (education and occupation). Respondents who abided by the five precepts of Buddhism and meditated on Buddhist holy days reported higher levels of happiness. Those who regularly expressed gratitude, gave an opportunity to others before oneself, and made donations were more likely to consider themselves happy compared with those who never or rarely engaged in these Buddhist-inspired practices. These findings support the idea that religiosity and spirituality play a relevant role in the level of happiness among Thai people.